KINGSTON’S THE WOMAN WARRIOR AND CHINA MEN: GENDERED CONSTRUCTION OF ABJECT THROUGH GHOSTS - Yovela, Stasya; Priyatna, Aquarini; Prabasmoro, Tisna (Universitas Padjadjaran, 2024)
The autobiographical works by Maxine Hong Kingston, The Woman Warrior: Memoirs of a Girlhood Among Ghosts (1989) and China Men (1989), portray a gendered construction of the abject through the ghosts of Kingston’s deceased family members in the novels. As Chinese descendants, the family should uphold a tradition of honoring their dead, feeding them food, and remembering them. However, Kingston’s family in the novels rejects their ghosts instead because the dead are thought to bring shame and discomfort to the family, who are now living as Americans. We see such ambiguity where the ghosts are simultaneously seen as part of the family yet also discomforting as related to the abject. By utilizing the framework of feminist narratology and theories of abjection, we see that the family abjects them by forgetting and not acknowledging them. These ghosts are part of the family but simultaneously expelled as the abject. However, despite all of the ghosts being the abject, we argue that their individual abjections vary based on their gender where the female ghosts and male ghosts are abjected differently. We argue that the abject constructed through the female ghosts is portrayed as disobedient, disturbing borders, and traumatic, whereas through the male ghosts is portrayed as passively expelled from a place of power and silenced. Despite all of the deceased being treated as outcasts, we see that the deceased women are able to reclaim subjectivity through their abjection, whereas the abjection from the male ghosts reflects ambiguity.